Leaving the Land of Digital Natives (2012)
Camilo Jiménez taught writing and literature at the prestigious Universidad Javeriana in Columbia for nine years until his resignation in December 2011, for reasons explained in this article. Written for the Universidad Javeriana communications department and for Jiménez’s blog- el ojo en la paja (the eye in the straw), http://elojoenlapaja.blogspot.com/- the piece elicited considerable response. On December 8, 2011, it was reprinted under the title “Camilo Jiménez, Journalist and Professor of Social Communication, Resigns His Position” in El Tiempo, Colombia’s most widely-read newspaper, where it received many, many more responses. The piece has been translated from the Spanish by Will H. Corral and Daphne Patai, professor of Brazilian literature and literary theory at the University of Massachusetts, Amherst. Prof. Corral also provides an introduction.